2007
DOI: 10.1253/circj.71.524
|View full text |Cite
|
Sign up to set email alerts
|

Role of Activated Renin-Angiotensin System in Myocardial Fibrosis and Left Ventricular Diastolic Dysfunction in Diabetic Patients Reversal by Chronic Angiotensin II Type 1A Receptor Blockade

Abstract: ype 2 diabetes mellitus is associated with an increased risk of cardiovascular disease. 1 In particular, diabetic patients have a higher incidence of congestive heart failure compared with age-matched non-diabetic subjects. 2 Although left ventricular (LV) systolic dysfunction occurs only infrequently, diastolic dysfunction is a commonly observed cardiovascular manifestation even in the absence of ischemic or hypertensive heart diseases in diabetic patients. 3,4 The pathogenesis of LV diastolic dysfunction is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 43 publications
(32 citation statements)
references
References 29 publications
0
31
0
1
Order By: Relevance
“…24) Activation of the cardiac renin-angiotensin system, myocardial stiffening associated with fibrosis, and abnormal microvascular function have been suggested as contributing to cardiac diastolic dysfunction in humans and animal models with diabetes and hypertension. 10,25,26) We reported that impairment of coronary microcirculation associated with activation of angiotensin type I receptor occurred in SHRSP-fatty. 8) In the present study, we found that collagen type I accumulated in the ventricles along with diastolic dysfunction in SHRSPfatty.…”
Section: Discussionmentioning
confidence: 99%
“…24) Activation of the cardiac renin-angiotensin system, myocardial stiffening associated with fibrosis, and abnormal microvascular function have been suggested as contributing to cardiac diastolic dysfunction in humans and animal models with diabetes and hypertension. 10,25,26) We reported that impairment of coronary microcirculation associated with activation of angiotensin type I receptor occurred in SHRSP-fatty. 8) In the present study, we found that collagen type I accumulated in the ventricles along with diastolic dysfunction in SHRSPfatty.…”
Section: Discussionmentioning
confidence: 99%
“…However, few studies have investigated potential therapies. In type 2 diabetic subjects with LVDD, 6 months' treatment with candesartan improved one index of diastolic filling (E/A), but not another (DT) (15). In hypertensive patients with LVDD, 12% of whom had diabetes, BP reduction over 38 weeks improved myocardial relaxation (EЈ) irrespective of the agent used, but the independent effect of diabetes was not assessed (16).…”
Section: Abp and Hrmentioning
confidence: 99%
“…[13][14][15] It is an important question to be solved whether the beneficial effects of valsartan on the MBV imply clinically relevant vascular protection for patients with HT, which will translate into improved outcomes, reduced morbidity and mortality. [22][23][24] We measured MBV during MCE as a noninvasive index of structural alterations of the myocardial microvasculature in vivo. There are several other techniques that also allow assessment of microvascular disease in the clinical setting.…”
Section: Discussionmentioning
confidence: 99%